2009
DOI: 10.1111/j.1567-1364.2008.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic13C-tracer study of storage carbohydrate pools in aerobic glucose-limitedSaccharomyces cerevisiaeconfirms a rapid steady-state turnover and fast mobilization during a modest stepup in the glucose uptake rate

Abstract: In this research, two dynamic (13)C-labeling experiments confirmed turnover and rapid mobilization of stored glycogen and trehalose in an aerobic glucose-limited chemostat (D=0.05 h(-1)) culture of Saccharomyces cerevisiae. In one experiment, the continuous feed to an aerobic glucose-limited chemostat culture of S. cerevisiae was instantaneously switched from naturally labeled to fully (13)C labeled while maintaining the same feed rate before and after the switch. The dynamic replacements of naturally labeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…The glycolytic intermediates reached isotopic steady states after about 10–15 minutes, which is high compared to the turnover time (data not shown) but a commonly observed delay [25,36,37]. The delay can be explained by exchange fluxes with big pools of trehalose and storage polymers such as glycogen.…”
Section: Resultsmentioning
confidence: 90%
“…The glycolytic intermediates reached isotopic steady states after about 10–15 minutes, which is high compared to the turnover time (data not shown) but a commonly observed delay [25,36,37]. The delay can be explained by exchange fluxes with big pools of trehalose and storage polymers such as glycogen.…”
Section: Resultsmentioning
confidence: 90%
“…C. glutamicum can store glycogen and maltodextrins during growth (45), as well as trehalose (46), and the catabolism of these components concomitantly with the metabolism of added labeled glucose leads to 13 C dilution, as demonstrated by the presence of unlabeled end products when uniformly labeled glucose was provided. This phenomenon has been observed in bacteria and yeast, which showed fast mobilization of carbohydrate storage pools (47,48). Moreover, the reverse flux from labeled glucose to reserves was apparent from the buildup of labeled glycogen and trehalose (see Fig.…”
Section: Discussionmentioning
confidence: 88%
“…It is frequently reported that the storage carbohydrates react rapidly to dynamic conditions, even under mild perturbations [33], thus during the feast/famine it might be expected these metabolites to exhibit a strong dynamic response. The metabolism of two major storage carbohydrates, trehalose and glycogen, was monitored through their intermediates (Figure 7).…”
Section: Resultsmentioning
confidence: 99%